2-Naphthol scaffold as selective colorimetric and fluorescence ‘turn-on’ sensor of PO43- - Mudi, Naren; Giri, Prabhat Kr.; Shekhar Samanta, Shashanka.; Mandal, Usha; Ramírez Tagle, Rodrigo.; Misra, Ajay (Taylor and Francis, 2023)
1-(Pyridin-2-yl-hydrazonomethyl)-naphthalen-2-ol (PNOH) is a naphthalene-based fluorescence chemo-sensor for PO43-. The probe (PNOH) is spectroscopically characterised and the chemo-sensing mechanism has been demonstrated through 1H NMR, UV-Vis absorption and both steady-state and time resolved fluorescence study. Fluorescence ‘turn-on’ sensing knack of PNOH towards PO43- ion has been explained due to emission from the excited PNO– ion, formed upon transfer of phenolic proton of PNOH to PO43- ion in the excited state. The 1:1 stoichiometry of PNOH-PO43- complex is observed from Job’s plot based on UV-Vis titration and the complex shows distinct yellowish-green colour to be used as colorimetric sensor for PO43-. Limit of detection (LOD) of PNOH towards PO43- is found to be 0.35 µM. It is also demonstrated that the probe can be used to fabricate a convenient and efficient PO43- paper test kits as well as molecular INHIBIT logic gate.
Keywords: PNOH; PO4 3-sensor; INHIBIT logic gate; paper strip